2024
DOI: 10.1038/s41593-023-01553-8
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic input and Ca2+ activity in zebrafish oligodendrocyte precursor cells contribute to myelin sheath formation

Jiaxing Li,
Tania G. Miramontes,
Tim Czopka
et al.

Abstract: In the nervous system, only one type of neuron-glial synapse is known to exist: that between neurons and oligodendrocyte precursor cells (OPCs), yet their composition, assembly, downstream signaling, and in vivo functions remain largely unclear. Here, we address these questions using in vivo microscopy in zebrafish spinal cord and identify postsynaptic molecules PSD-95 and Gephyrin in OPCs. The puncta containing these molecules in OPCs increase during early development and decrease upon OPC differentiation. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 73 publications
1
3
0
Order By: Relevance
“…Since their discovery two decades ago, the temporal dynamics of neuron-OPC synapses have been unknown and only recently investigated ( Bergles et al, 2000 ). By tracking the lifetime of PSD-95 and Gephryn in oligodendrocyte processes, Li et al (2024) observed these complexes persisted on average 5–15 min, which is similar to the durations of interactions tracked in our study. These findings by Li et al demonstrate that oligodendrocyte process extensions containing postsynaptic proteins may form synapse-like interactions with axons that are transient in nature.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Since their discovery two decades ago, the temporal dynamics of neuron-OPC synapses have been unknown and only recently investigated ( Bergles et al, 2000 ). By tracking the lifetime of PSD-95 and Gephryn in oligodendrocyte processes, Li et al (2024) observed these complexes persisted on average 5–15 min, which is similar to the durations of interactions tracked in our study. These findings by Li et al demonstrate that oligodendrocyte process extensions containing postsynaptic proteins may form synapse-like interactions with axons that are transient in nature.…”
Section: Discussionsupporting
confidence: 87%
“…In contrast, Li et al designed time-lapse experiments to track the fates of Gephryn-containing complexes in oligodendrocyte process for up to 16 h. This long-term tracking revealed that Gephryn-containing complexes were predictive of where processes later matured into sheaths. Furthermore, the probability that Gephryn-containing processes formed sheaths was reduced by tetanus neurotoxin treatment, suggesting that synaptic vesicle release enables oligodendrocytes to determine which contacts should mature to form myelin sheaths ( Li et al, 2024 ). In a separate study, Wake et al (2015) reported that synaptic vesicle release blockade reduced local MBP translation and intracellular Ca2+ elevations that occurred within processes interacting at axon varicosities.…”
Section: Discussionmentioning
confidence: 99%
“…OPCs receive synaptic inputs from both excitatory and inhibitory neurons [ 43 45 ]. These synapses have been recently shown to be important for myelination and OPC development in zebrafish [ 46 ]. An intriguing hypothesis is that C1QL1/BAI3 signaling could participate in the regulation of neuron-OPC synapses and their control of myelination.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the absence of microglia diminished OPC engulfing activity, suggesting a signal input from microglia for OPC phagocytosis ( 21 ). As OPCs form postsynaptic structures with neuronal axons, and neurotransmission via this communication triggers OPC differentiation into mature oligodendrocytes—cells that do not inherit synaptic connections ( 35 , 36 )—it is plausible that after receiving signals for differentiation, OPCs phagocytose presynaptic terminals projected to them, ultimately differentiate into mature oligodendrocytes. However, further studies are needed to validate this hypothesis.…”
Section: Threat Elimination Through Phagocytosismentioning
confidence: 99%